ANALYSIS OF THE IMAGE OF "HORSE" IN THE WORK OF “THE HEADLESS HORSEMAN” BY THOMAS MAYNE REID - Ochilova Nilufar Ulmasovna (Scholar Express Journal, 2023)
“The Headless Horseman” by Maine Reid conveys special significance to the image of “horse” which the work acquired a deeper meaning. This figure is in modern English and Uzbek literature which is adapted to realism, expressed in harmony with the scenes of national life. In this article, the image of “horse” in “The Headless Horseman” by Thomas Mayne Reed is interpreted from artistic and comparative aspects.
Keywords: The image of horse; mustang; mustang rider; stallion